Goursat-Type Problem for a Higher-Order Equation - Yusubov, Sh. Sh. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
For a higher-order equation with leading mixed derivative, we consider the Goursat-type problem without consistency conditions. The notion of fundamental solution is introduced. By using this notion, we obtain a representation of the solution of the analyzed problem.